Organizational Demography: The Differential Effects of Age and Tenure Distributions on Technical Communication - Zenger, Todd; Lawrence, Barbara (Academy of Management Journal, 1989)
Although previous researchers have proposed organizational demography as an important determinant of communication, no one has tested this relationship directly. Further, distinctions between the impacts of different demographic variables on communication have not been explored. This study used sociometric data collected from a U.S. electronics firm to examine such relationships. The results show a relationship between age and tenure distributions and the frequency of technical communication. Moreover, the results suggest that inside project groups, age distributions exert greater influence than tenure distributions on the frequency of technical communication but that the reverse relationship holds for technical communication outside project groups.